ANCUR PODCAST DIGITAL IDENTITY AS AN EFFORT TO CREATE AN IMAGE - Imam Zuliantripa; Nofha Rina (International Journal of Cultural and Social Science, 2026)
This study aimed to analyze the formation of digital identity in the Ancur Podcast as an independent podcast operating in a digital media environment. The development of podcast platforms has transformed podcasts into interactive communication spaces, where identities are formed and interpreted through interactions between creators and audiences. This research used a qualitative approach with a narrative method. Data was collected through in- depth interviews with the Ancur Podcast creator team and active audiences, as well as content analysis on various digital platforms. The results of the study show that the digital identity of the Ancur Podcast is formed through a dynamic and continuous process. These identities are not singular or static, but fragmented according to the characteristics of the platform and the pattern of audience engagement. The formation of digital identity of the Ancur Podcast consists of three main dimensions, namely declared identity, acting identity, and calculated identity. In addition, the image of the Ancur Podcast is strengthened by the factors of strength, favorability, and uniqueness which are built through the consistency of communication styles, positive perceptions of the audience, and collective identity in the listener community. This study concluded that digital identity plays a role as a strategic asset in communication that contributes to the formation of an image and the sustainability of relationships with audiences on independent podcasts.